Synthesis and structure of KInP2O7 obtained from K—In—P—Mo—O melts - Kyselov, D.V.; Terebilenko, K.V.; Petrenko, O.V.; Baumer, V.N.; Slobodyanik, M.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
The peculiarities of the crystallization from mixed phosphate — molybdate melts and the structure of KInP2O7 have been investigated. The compound crystallizes in a monoclinic system, space group P21/c(14),a=7.4092(1),b=10.3990(1),c=8.3966(1),β=106.23(0)°,V=621.16(36)Å3. The three-dimensional framework [InP2O7]∞ consists of isolated InO6 octahedra interlinked by six pyrophosphate groups. This type of architecture of the anionic sublattice forms hexagonal channels, where potassium cations are located. Doping the host studied with rare-earth metals would open a possibility of its practical application as a base of the phosphors.